A randomized clinical trial of a financial education intervention with nicotine replacement therapy (NRT) for low socio‐economic status Australian smokers: a study protocol. (18th July 2014) - Courtney, Ryan J.; Bradford, Deborah; Martire, Kristy A.; Bonevski, Billie; Borland, Ron; Doran, Christopher; Hall, Wayne; Farrell, Michael; Siahpush, Mohammad; Sanson‐Fisher, Rob; West, Robert; Mattick, Richard P.
Abstract Background and Aims Reducing smoking prevalence among smokers from low socio‐economic status (SES) is a preventative health priority. Financial stress (e.g. shortage of money or inability to pay bills) may be a major barrier to quitting smoking. This study evaluates the efficacy of a financial education and support programme coupled with pharmacotherapy at improving cessation rates at 8‐month follow‐up among Australian low SES smokers (people receiving a government pension or allowance). Design A two‐group parallel block randomized (ratio 1 : 1) open‐label clinical trial (RCT) with allocation concealment will be conducted. Allocation will be concealed to interviewers at data collection‐points. Setting The study will be conducted primarily by telephone with baseline, follow‐up interviews and telephone‐based support sessions. Nicotine replacement therapy (NRT) delivery will be mail‐based. Participants Daily smokers who are interested in quitting smoking and are currently in receipt of government benefits (n = 1046) will be recruited through study advertisements placed in newspapers, posters placed in government social assistance agencies and Quitline telephone‐based cessation support services. After completion of a baseline computer‐assisted telephone interview, participants will be allocated randomly to control or intervention group using a permuted block approach. Intervention and Comparator Participants in both groups will receive 8 weeks of free combination NRT plus Quitline support. Participants in the intervention group will also receive four telephone‐delivered financial education and support sessions. Measurements The primary outcome measure will be prolonged abstinence (at 8‐month follow‐up) assessed using Russell Standard criteria and biochemically verified (urine cotinine). Comments This is the first intervention study to evaluate the potential of co‐managing financial stress as a means of enhancing smokers' capacity to quit smoking. Such an intervention may provide a scalable intervention to help low SES smokers to quit.